Teori Belajar Popular dalam Model Quantum Learning: Array - Nur Khofifah; Neviyarni; Herman Nirwana (eductum: Jurnal Literasi Pendidikan, 2022)
The Learning Model discusses articles about Quantum Learning. Quantum Learning can provide benefits to students. It cannot be denied that the learning model can remember and capture what the teacher gives to students. The theory of Quantum Learning is a learning model for why learning is set. learning that can achieve the learning objectives that have been set. This strategy in Quantum Learning is by using books, an effective atmosphere in the classroom.